Hydro-mechanical reinforcements of live poles to slope stability - Viroon Kamchoom; Anthony K. Leung (My University, 2018)
Soil bioengineering using live poles is an environmentally friendly technique for shallow slope stabilisation. However, it remains unclear in this technique whether the hydrological effects of pole transpiration are significant to slope stabilisation, compared to mechanical reinforcement by structural poles and their fibrous roots. The aims of this study were to investigate the hydro-mechanical reinforcement effects of live poles and to evaluate their effectiveness for shallow slope stabilisation, giving due consideration to the different pole growth stages. Finite-element seepage-stability models were developed and validated against centrifuge model tests that investigated the rainfall-induced instability of a 45-degree clayey sand slope subjected to intense rainfall. The short-term stability right after the installation of the poles is critical because only structural poles, i.e., without fibrous root reinforcement or water uptake, are insufficient for reinforcement, even those as long as 2 m. Due to the absence of pole transpiration, positive pore water pressure of up to 10 kPa was built up near the slope toe, causing the significant mobilisation of shear strain and consequentially slope failure. In longer term, during which fibrous roots developed and provided additional mechanical reinforcement (via root cohesion) and transpiration-induced suction, no slope failure occurred due to the considerable amount of suction that was retained within the pole zone. It was mainly the pole transpiration before the rainfall, i.e., antecedent drying, that retained the suction, rather than the transpiration that took place during the rainfall.
Keywords: Centrifuge; Cohesion (chemistry); Tree Root and Stability Studies